FIND OPTIMAL PRICES IN AREA WITH THREE INVENTORY METHOD OF TRANSPORTATION - Indriani Indriani; Ir. Jalinas Ir. Jalinas (Jurnal Sistem Informasi, 1997)
Transportation method is a method used to regulate the distribution of the sources thatprovide the same products and also aims to meet the minimum total cost.Transportation method can also be used in the world and usaha.Menggunakan VogelsApproximation Methods will be faster in terms of allocation of some resources to thedestination area